Prenatal Diagnosis and Management of Ectopia Cordis: Varied Presentation Spectrum. (4th March 2019) - Türkyilmaz, Gürcan; Avcı, Sahin; Sıvrıkoz, Tugba; Erturk, Emircan; Altunoglu, Umut; Turkyilmazlmaz, Sebnem Erol; Kalelioglu, Ibrahim Halil; Has, Recep; Yuksel, Atil
Abstract: Background : Ectopia cordis (EC) is a congenital anomaly associated with heart defects and extracardiac malformations. Objectives : We determined the various presentations of EC diagnosed in our center between 2010 and 2017. Results : Seven fetuses from six pregnancies with EC were detected, five during the first trimester. Three were from multiple pregnancies, and both twins had EC in one monochorionic-monoamniotic pregnancy. Abdominal wall defects were detected in six fetuses. Kyphoscoliosis, cephalocele, clubfoot and short umbilical cord were other abnormalities. Five fetuses were terminated, one fetus died in utero, and one baby died on day two of life. Postnatal evaluation performed in all cases additionally detected cleft lips/palates in two fetuses and tetralogy of Fallot in one. Conclusion : Outcome is poor for these fetuses, EC can occur in a multiple pregnancy, most of the abnormalities can be identified in the first trimester and fetopsy continues to add information to the intrauterine diagnosis.